2018
DOI: 10.1371/journal.pone.0195967
|View full text |Cite
|
Sign up to set email alerts
|

Water system is a controlling variable modulating bacterial diversity of gastrointestinal tract and performance in rainbow trout

Abstract: A two-phase feeding study evaluating performance of rainbow trout and comparing luminal and mucosal gastrointestinal tract (GIT) bacterial community compositions when fed two alternative protein diets in two rearing systems was conducted. Alternative protein diets (animal protein and plant protein diets) balanced with crystalline amino acids: lysine, methionine and threonine or unbalanced, were fed to rainbow trout in two separate water systems (recirculating (RR) and flow-through (FF)) for a period of 16 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 53 publications
0
6
1
Order By: Relevance
“…Notwithstanding the fact that different extraction methods can cause small variations in the microbial profile (Wagner Mackenzie et al, 2015) studies have shown that rearing water has a minor effect on the GI microbiota in fish (Giatsis et al, 2015; Uren Webster et al, 2018). Betiku et al (2018) have demonstrated that recirculating water systems have more diverse microbial composition compared to the flow-through system. However, similar to other reports (Yan et al, 2016, Lokesh et al, 2018, Gupta et al, under review) water bacterial communities might not have affected the intestinal bacterial profile in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the fact that different extraction methods can cause small variations in the microbial profile (Wagner Mackenzie et al, 2015) studies have shown that rearing water has a minor effect on the GI microbiota in fish (Giatsis et al, 2015; Uren Webster et al, 2018). Betiku et al (2018) have demonstrated that recirculating water systems have more diverse microbial composition compared to the flow-through system. However, similar to other reports (Yan et al, 2016, Lokesh et al, 2018, Gupta et al, under review) water bacterial communities might not have affected the intestinal bacterial profile in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the anterior and posterior sections it was observable genera like Clostridiales in Control-A but was not present in FH-A. In the posterior section, Enhydrobacter appearedin the treatment FH-P. Enhydrobacter is present in the microbiota of fish such as Dicentrarchus labrax and Salmo trutta 57 . It is known that this genus utilizes certain amino acids such as l -arginine, l -serine and l -alanine 58 , while some species present cellulase activity 57 , 59 .…”
Section: Discussionmentioning
confidence: 97%
“…In the posterior section, Enhydrobacter appearedin the treatment FH-P. Enhydrobacter is present in the microbiota of fish such as Dicentrarchus labrax and Salmo trutta 57 . It is known that this genus utilizes certain amino acids such as l -arginine, l -serine and l -alanine 58 , while some species present cellulase activity 57 , 59 . This fact may be of interest as cellulases hydrolyze the cellular wall of N. gaditana , allowing the fish to absorb the intracellular compounds of this algae.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Büyükdeveci et al [ 20 ] showed an increase in body weight and a decrease in alpha diversity as the garlic concentration increased in the diet of rainbow trout ( O. mykiss ). However, another study on rainbow trout ( O. mykiss ) by Betiku et al [ 76 ] suggested that increased body weight is related to higher bacterial diversity. Although in our study, the general structure of bacterial community did not differ between the control and Allium -derived PTSO treatment, we found significant differences in the hindgut when the most abundant ASVs were taken into account.…”
Section: Discussionmentioning
confidence: 99%